Sustainable Financing Ecosystem in Islamic Higher Education: Integrating Community Participation and Distributive Justice Principles - Dika Tripitasari; Dewi Ratnawati (CV. Bimbingan Belajar Assyfa, 2026)
The escalating cost of higher education and the limitations of state funding have created a critical need for sustainable and equitable financing models in Islamic institutions. This study aims to analyze the implementation of a community-based financing management system designed to achieve educational equity at the State Islamic Institute (IAIN) Parepare. Employing a qualitative approach with a case study design, data were gathered through in-depth interviews with university leaders, financial administrators, and students, alongside an analysis of digital financial reports. The findings reveal a robust financing ecosystem integrated through three strategic pillars: the digitalization of financial governance via the e-Monev system to ensure transparency, the implementation of tiered tuition fee (UKT) policies grounded in Islamic distributive justice, and the optimization of participatory funding through Islamic philanthropy, such as cash waqf and zakat. Results indicate that this model significantly reduced dependence on government budgets, with non-state revenue increasing from 45% to 79% over three years. The study concludes that integrating community participation with spiritual values like amanah and ihsan creates a resilient financial structure that safeguards access for underprivileged students. These implications suggest that Islamic higher education institutions can achieve financial sustainability by fostering a